2008
DOI: 10.1111/j.1365-2184.2008.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of cord blood‐derived unrestricted somatic stem cells in tissue engineering concepts

Abstract: USSCs when transplanted into a bone defect might support the repair process not only by pure remineralization but also by installation of angiogenic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Furthermore, their use does not raise ethical concerns [2,33,34] . The differentiation potential of USSCs into the osteogenic lineage is well known and has been verified by many research groups [36,40,41] . They can be differentiated into the osteogenic lineage both spontaneously and when cultured with specific supplements [36] .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, their use does not raise ethical concerns [2,33,34] . The differentiation potential of USSCs into the osteogenic lineage is well known and has been verified by many research groups [36,40,41] . They can be differentiated into the osteogenic lineage both spontaneously and when cultured with specific supplements [36] .…”
Section: Discussionmentioning
confidence: 80%
“…In an experiment by Babister et al [1] , both the activity and the transcription of ALPase in hMSCs were highest on d 21. Conversely, Degistirici et al [41] found that USSCs expressed the most active ALPase on d 7 during osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 95%
“…As USSCs also show a high production of VEGF and FGF2 and express VEGF Receptor-2 the transplantation into a bone or tissue defect might support the repair process not only by initiating mineralization but also by creating an angiogenic environment. 64 …”
Section: Characterization Of Non-adherent Cells From Fresh and Cryoprmentioning
confidence: 99%
“…In addition, other investigators [57][58][59][60][61] and our group [61][62][63][64][65][66] showed that USSC can be stimulated to differentiate into cells of the three germ layer lineages, endodermal, ectodermal and mesodermal [62]. USSCs have an initial population doubling time of about 39 h, which decreased only slightly with increasing passage number, but cells maintained their proliferation abilities up to passage 23.…”
Section: Embryonic Sc (Esc) Trans-differentiationmentioning
confidence: 89%
“…[46] who recommend 10% FCS for CB-MSC in vitro-expansion, own experiences have shown advantages for higher FCS concentations supplemented by 10 −5 -10 −7 M dexamethasone [62]. Following this cultivation protocol colony forming units will appear after 5-10 days after initial cultivation.…”
Section: Embryonic Sc (Esc) Trans-differentiationmentioning
confidence: 99%